Dinamika hukum adat dan agama di Aceh - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Abstract The specialty ofAceh lies on the application of customs law, religion and education. Those three aspects color the way of lift for the Acehnese. Viewed from New Regime, Acehnese had to apply state laws and, as a result, they ignored them. The change of the status from Special Province of Aceh to Nanggroe Aceh Darrussalam is hope to bring positive results because adapt law and institutions can be practiced again.